Sistem Pakar dalam Mengidentifikasi Penyakit pada Sapi Bali Menggunakan Metode Certainty Factor - M Rasyid; S Sumijan (Jurnal Informasi dan Teknologi, 2021)
Bali cattle are livestock that are very easy to maintain and the price is economical. Most of the people of Kampar Regency, Riau Province, keep cattle with the type of Bali cattle. The difficulty that is often experienced by Balinese cattle breeders is the disease that attacks Bali cattle. Lack of knowledge of breeders in diseases that attack Bali cattle resulted in the death of Bali cattle due to lack of handling and farmers suffered losses. The purpose of this study is to create an expert system that can assist veterinarians, animal health workers in identifying early diseases that attack Bali cattle and how to treat them early. To make it easier to identify diseases in Bali cattle, the method used in this study is the Certainty Factor (CF) method, where this method proves a fact in an incident based on evidence from experts. The data processed in this study were 6 types of diseases. The results of this study produce a value for the level of certainty of a disease that attacks Bali cattle and can assist veterinarians in identifying the types of diseases in Bali cattle.